2019
DOI: 10.1186/s12889-019-6548-0
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing basic vaccination coverage in Myanmar: secondary analysis of 2015 Myanmar demographic and health survey data

Abstract: Background Immunization is one of the most effective measures for preventing disease when vaccination coverage is sufficient. Although vaccination coverage is known to be influenced by social and cultural barriers, the determinants of childhood immunization in Myanmar remain poorly understood. This study analyzed factors that influenced complete vaccination status (one dose each for Bacillus Calmette-Guérin and measles and three doses each for diphtheria-pertussis and polio) using 2015 data from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
56
2
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(81 citation statements)
references
References 32 publications
15
56
2
5
Order By: Relevance
“…Similarly, mothers who took TT vaccination were almost five times more likely to complete vaccination for their children compared to those who were not vaccinated. This finding is comparable with a study done in Myanmar [ 84 ] that revealed an association between TT vaccination and immunization coverage among children 12–23 months. Maternal service utilization such as ANC and TT vaccinations are found to be proxy indicators that enhanced 19 and 13% immunization coverage among children aged 12–23 months respectively [ 88 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similarly, mothers who took TT vaccination were almost five times more likely to complete vaccination for their children compared to those who were not vaccinated. This finding is comparable with a study done in Myanmar [ 84 ] that revealed an association between TT vaccination and immunization coverage among children 12–23 months. Maternal service utilization such as ANC and TT vaccinations are found to be proxy indicators that enhanced 19 and 13% immunization coverage among children aged 12–23 months respectively [ 88 ].…”
Section: Discussionsupporting
confidence: 91%
“…Mothers who followed ANC were more likely to complete vaccination for their children compared to their counterparts. This finding is in line with studies conducted in Pakistan [ 73 ], Myanmar [ 84 ] Indonesia [ 78 ], Senegal [ 59 ] India [ 85 ], and Philippines [ 86 ], and a study done in 46 low and middle income countries (LMIC) [ 87 ]. Mothers who are following both ANC and PNC are more likely to interact with health care providers and exposed to information about maternal and newborn health services [ 78 ].…”
Section: Discussionsupporting
confidence: 90%
“…El seguimiento prenatal adecuado se asocia a menor número de complicaciones obstétricas como a concientizar a la madre sobre cuidados y conductas pertinentes a seguir en la gestación, siendo los principales; el cumplimiento de las inmunizaciones y los controles prenatales (8,13) . En el Perú según el MINSA los controles prenatales tienen que ser mínimo 6 CPN para considerar adecuado seguimiento y garantizar el bienestar de bebe si son menos o ningún control prenatal puede generar alto riesgo para la madre como él bebe por lo cual muchas veces afecta el desarrollo (8) .…”
Section: Discussionunclassified
“…Moreover, policies and implementations of immunization programs vary substantially across countries. For instance, the national immunization coverage for MCV1 in Myanmar was lower than that in China in 2015 (86% versus 99%) [ 10 , 11 ]. A study from China in 2017 also showed that measles antibody level among Myanmar migrants was lower than that among local residents [ 12 ].…”
Section: Introductionmentioning
confidence: 99%